History and development of ophthalmology in Taiwan - Yu-Chih Hou; Gale A. Oren; Muh-Shy Chen; Fung-Rong Hu (Journal of the Formosan Medical Association, 2016)
Western medicine was first introduced to Taiwan by medical missionaries in the mid-19th century. Modernization of medicine was systematically transplanted to Taiwan in the Japanese colonial period, and ophthalmology was established third among hospital departments, following internal medicine and surgery. Dr Hidetaka Yamaguchi, an ophthalmologist, was the first head of the Taihoku Hospital, later known as National Taiwan University Hospital (NTUH; Taipei, Taiwan). Ophthalmologists during the colonial period conducted studies on tropical and infectious eye diseases. After World War II, ophthalmologists at NTUH played an important role in medical education, residency training, studies, and teaching. Dr Yan-Fei Yang established the Taiwan Ophthalmological Society in 1960 and instituted its official journal in 1962. Dr Ho-Ming Lin established the Department of Ophthalmology at the Tri-Service General Hospital in the 1950s and the Veterans General Hospital in the 1960s. Taiwan ophthalmologists eradicated trachoma by 1971. Cataract surgery and penetrating keratoplasty were initially performed in the 1960s. Currently, there are about 1600 ophthalmologists in Taiwan conducting an estimated 120,000 cataract surgeries and 600 corneal transplantations annually. Many subspecialty societies have been established recently that serve to educate Taiwanese ophthalmologists and to connect with international ophthalmic societies. Taiwan ophthalmologists continue to contribute to the advancement of ophthalmic knowledge globally.